1989
DOI: 10.1002/jcp.1041390102
|View full text |Cite
|
Sign up to set email alerts
|

Mutual contact of murine erythroleukemia cells activates depolarizing cation channels, whereas contact with extracellular substrata activates hyperpolarizing Ca2+‐dependent K+ channels

Abstract: This study deals with the modulation of the plasma membrane potential (delta psi p) of murine erythroleukemia (MEL) cells by cell-substratum or cell-cell contact. delta psi p was determined by measuring the distribution of tetraphenylphosphonium (TPP+) across the plasma membrane; it appeared strongly, and inversely, influenced by the two types of cell contacts. Contact with the culture surface produced a delta psi p hyperpolarization directly proportional to average distance among the ideal centers of the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Integrin-induced membrane hyperpolarization has been reported in other cell types (Arcangeli et al 1987(Arcangeli et al , 1989Hofmann et al 2001), but our results provide the first evidence that BK channel activation may be a key underlying mechanism in VSM. Arcangeli and colleagues first reported that FN-integrin interactions elicited hyperpolarization of murine erythroleukaemia cells (Arcangeli et al 1991), an effect presumably mediated by the activation of Ca 2+ -activated K + channels (Arcangeli et al 1987(Arcangeli et al , 1989. The same group has also shown that the activation of β1 integrins in neuroblastoma and haemopoietic tumour cells leads to sustained activation of hERG K + current (Hofmann et al 2001).…”
Section: Coordinated Regulation Of Bk and Ca 2+ Channels By α5β1 Intesupporting
confidence: 49%
“…Integrin-induced membrane hyperpolarization has been reported in other cell types (Arcangeli et al 1987(Arcangeli et al , 1989Hofmann et al 2001), but our results provide the first evidence that BK channel activation may be a key underlying mechanism in VSM. Arcangeli and colleagues first reported that FN-integrin interactions elicited hyperpolarization of murine erythroleukaemia cells (Arcangeli et al 1991), an effect presumably mediated by the activation of Ca 2+ -activated K + channels (Arcangeli et al 1987(Arcangeli et al , 1989. The same group has also shown that the activation of β1 integrins in neuroblastoma and haemopoietic tumour cells leads to sustained activation of hERG K + current (Hofmann et al 2001).…”
Section: Coordinated Regulation Of Bk and Ca 2+ Channels By α5β1 Intesupporting
confidence: 49%
“…These cells express Ca 2+ -dependent K + channels (BK Ca ) [24,25] that are transiently activated when differentiation is stimulated by cell adhesion onto fibronectin [26,27], or by application of classical inducers of erythroid differentiation [28]. Similar effects were observed in THP-1 human monocytic leukemia cells.…”
Section: The Expression and Biological Roles Of Ion Channels In Leukementioning
confidence: 73%
“…This is likely important since cell migration requires that integrins undergo numerous cycles of attachment and release. Integrin-toligand binding causes K ϩ channel activation (Arcangeli et al, 1989(Arcangeli et al, , 1991(Arcangeli et al, , 1996Becchetti et al, 1992), which may enhance Ca 2ϩ influx. For example, inhibition of K ϩ channels by TEA, 4-AP, and verapamil block Ca 2ϩ influx (Lepple-Wienhues et al, 1996;Yao and Kwan, 1999).…”
mentioning
confidence: 99%
“…Hyperpolarization precedes a marked cell spreading in erythroleukemia cells (Arcangeli et al, 1991) and serves as a commitment signal to neuritogenesis in neuroblastoma cells (Arcangeli et al, 1993). Fibronectin binding promotes activation of Ca 2 ϩ -dependent K ϩ channels in murine erythroleukemia cells, HERG K ϩ channel currents in human preosteoclastic leukemia cells, and inwardly rectified K ϩ channels in neuroblastoma cells (Arcangeli et al, 1989(Arcangeli et al, , 1991Becchetti et al, 1992;Hofmann et al, 2001). Laminin also promotes inwardly rectifying K ϩ currents in neuroblastoma cells (Arcangeli et al, 1996).…”
mentioning
confidence: 99%